2016
DOI: 10.1097/wnn.0000000000000084
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral Disturbances During Acute and Early HIV Infection

Abstract: Background and Objective Acute and early human immunodeficiency virus infection (AEH) is accompanied by neuroinflammatory processes as well as impairment in neurocognitive and everyday functions, but little is known about the frequency and clinical correlates of the neurobehavioral disturbances during this period. We compared pre-seroconversion with current levels of apathy, disinhibition, and executive dysfunction; we also examined everyday function and HIV disease correlates of neuropsychiatric impairment in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 53 publications
(89 reference statements)
2
18
0
5
Order By: Relevance
“…Instead, there was an additive effect such that being HIV seropositive and having a clinical identification of MetS were independently associated with greater apathy and executive dysfunction, and there was a significant effect of HIV serostatus only on disinhibition. The presence of greater difficulties with neurobehavioral disturbances in PLWH compared to the HIV-uninfected comparison group aligns with previous research (Kamat et al 2016a;Kamat et al 2012). When looking at the frontalsubcortical circuits that may be affected, neuroimaging research has documented links between damage to the anterior cingulate cortex, dorsolateral prefrontal cortex, and orbital frontal cortex with difficulties with apathy, executive dysfunction, and disinhibition, respectively (Bonelli and Cummings 2007;Cummings 1993).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Instead, there was an additive effect such that being HIV seropositive and having a clinical identification of MetS were independently associated with greater apathy and executive dysfunction, and there was a significant effect of HIV serostatus only on disinhibition. The presence of greater difficulties with neurobehavioral disturbances in PLWH compared to the HIV-uninfected comparison group aligns with previous research (Kamat et al 2016a;Kamat et al 2012). When looking at the frontalsubcortical circuits that may be affected, neuroimaging research has documented links between damage to the anterior cingulate cortex, dorsolateral prefrontal cortex, and orbital frontal cortex with difficulties with apathy, executive dysfunction, and disinhibition, respectively (Bonelli and Cummings 2007;Cummings 1993).…”
Section: Discussionsupporting
confidence: 83%
“…These neurobehavioral disturbances have been empirically linked to frontal-subcortical dysregulation and central nervous system disease and may be present in the absence of neurocognitive impairment (Bonelli and Cummings 2007;Cummings 1993;Grace et al 1999;Ready et al 2003). Previous research has shown a consistent link between HIV serostatus and increased neurobehavioral disturbances, particularly increased apathy (e.g., diminished self-initiation, blunted affect), disinhibition (e.g., impulsivity and problems with self-regulation), and executive dysfunction (e.g., difficulties with successfully performing goal-driven behavior) (Castellon et al 1998;Kamat et al 2016a;Kamat et al 2012;Marquine et al 2014). However, no studies have investigated the role of MetS on neurobehavioral disturbances associated with HIV.…”
Section: Introductionmentioning
confidence: 99%
“…The hypothesis of early ACC dysfunction in HIV‐disease is also supported by the high prevalence of apathy in HIV (Paul et al, ; Walker & Brown, ), even in those with acute infection (Kamat et al, ). Neuropsychology studies (Cummings, ) have revealed a direct link between apathy and lesions to the ACC, suggesting the high prevalence of apathy in HIV might be associated with the highly prevalence of ACC injury.…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, the CLE meta‐analysis technique reveal evidence suggesting that in the cART era, the frontal cortex may be the most consistently affected brain region in HIV+ adults (compared to HIV− controls), especially in cognitively “normal” HIV+ individuals, suggesting that the frontal cortex might be affected early on in HIV‐disease, in line with previous studies using different imaging techniques that have identified frontal injury shortly after seroconversion (Peluso et al, ; Young et al, ). The high prevalence of frontal atrophy may directly contribute to the highly prevalent executive dysfunction in the cART era (Heaton et al, ), and may underlie early and more subtle neurocognitive impairment in HIV+ adults (Kamat et al, ; Prakash et al, ). However, within the frontal lobe, we do not detect a single subregion that is significantly more likely to be affected than other subregions, suggesting that GM atrophy in the frontal lobe might be widespread and diffuse, which in turn implicate that the impacts of frontal atrophy on neurocognitive performance might be diverse, and probably subtle (i.e., not always easily detectable).…”
Section: Discussionmentioning
confidence: 99%
“…Defined as the lack of cognitive, physical, and emotional motivation, apathy is exacerbated in early HIV infection (Kamat et al, in press) and occurs in an estimated 40% of chronically infected HIV+ persons (e.g. Kamat, Woods, Marcotte, Ellis, & Grant, 2012).…”
mentioning
confidence: 99%